Pattern of Presentation of Moyamoya Disease (MMD) Patients in Bangladesh: Experience from Tertiary Care Hospitals (Bangladesh Journal of Neuroscience, 2017)
Background: Moyamoya disease is rare but not uncommon throughout the world. Clinical profile of childhood moyamoya (MMD) disease is not well delineated in Bangladesh.Methods: We conducted this cross sectional study in pediatrics and neurology department of Dhaka Medical College Hospital that involved 20 patients of MMD over a period of one year.Result: Among the cases about 2/3rd(65%) of the patients were within 8 years age at onset with mean age of the patients being 7.24(±3.34) years at onset with a male: female ratio of 1.2:1. Almost half of the patients had past history of intermittent episodes TIA which precipitated by hyperventilation and crying (p